2020
DOI: 10.2174/1570159x17666191118125018
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrion as a Selective Target for the Treatment of Atherosclerosis: Role of Mitochondrial DNA Mutations and Defective Mitophagy in the Pathogenesis of Atherosclerosis and Chronic Inflammation

Abstract: Background: Atherosclerosis is a chronic inflammatory condition that affects different arteries in the human body and often leads to severe neurological complications, such as stroke and its sequelae. Affected blood vessels develop atherosclerotic lesions in the form of focal thickening of the intimal layer, so called atherosclerotic plaques. Objectives: Despite the high priority of atherosclerosis research for global health and the numerous preclinical and clinical studies conducted, currently there is no e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
48
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 50 publications
(52 citation statements)
references
References 74 publications
2
48
0
2
Order By: Relevance
“…According to the revised hypothesis, the proinflammatory response could be an inductor of the intracellular lipid accumulation (Figure 3) [57]. This hypothesis involves not only lipid accumulation and proinflammatory response, but also underlines the crucial role of phagocytosis in the aforementioned relation.…”
Section: Proinflammatory Response As An Inductor Of Intracellular Lipmentioning
confidence: 95%
“…According to the revised hypothesis, the proinflammatory response could be an inductor of the intracellular lipid accumulation (Figure 3) [57]. This hypothesis involves not only lipid accumulation and proinflammatory response, but also underlines the crucial role of phagocytosis in the aforementioned relation.…”
Section: Proinflammatory Response As An Inductor Of Intracellular Lipmentioning
confidence: 95%
“…Such mutations could be homoplasmic (absence or presence of the mutation) or heteroplasmic (different proportions of mutant allele). Another recent study identified variants of mtDNA that uncoupled oxidative phosphorylation: m.del562G, m.1555A>G, m.14459G>A, and m.14846G>A. Variants of mtDNA that sustained ATP synthase activity were m.3256C>T, m.12315G>A, and m.13513G>A [110]. The m.14459G>A mtDNA variant was associated with a higher basal rate of oxygen consumption.…”
Section: Mitochondrial Dysfunction and Mtdna Mutations In Chronic Patmentioning
confidence: 97%
“…A recent study conducted by our group has reported a relationship between mitochondrial functions and atherosclerosis-associated mtDNA mutations investigated on cybrid cell lines carrying various variants of the mitochondrial genome obtained from atherosclerotic patients [110]. Earlier studies of mtDNA obtained from the leukocytes of atherosclerotic patients revealed a correlation between certain mtDNA mutations and atherosclerosis [111][112][113].…”
Section: Mitochondrial Dysfunction and Mtdna Mutations In Chronic Patmentioning
confidence: 99%
See 1 more Smart Citation
“…При этом опыт, накопленный, начиная с первых работ Н.Н. Аничкова [3], демонстрирует, что атеросклеротическое повреждение сосудистой стенки является длительным многофакторным процессом [4]. В соответствии с современным пониманием патогенеза сердечно-сосудистых заболеваний, интеграль-ную роль в развитии атеросклероза и связанных с ним осложнений играет эндотелиальная дисфункция (ЭД) [5][6][7].…”
unclassified